CLINICAL AND HISTOPATHOLOGICAL CHARACTERISTICS OF PRIMARY BRAIN TUMOR DISEASE IN RSUP DR. KARIADI SEMARANG - Madani Hastutyosunu; Trianggoro Budisulistyo; Arinta Puspita Wati (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Introduction: Primary brain tumour is one of the non-communicable diseases that ranks 17th of all types of cancer in the world with an estimated 256,000 new cases each year. The incidence in North America, Europe and Australia is quite high with an estimated 4-8 new cases per 100,000 population per year. The incidence in continental countries of Asia and Africa is less compared to developed countries. The low incidence and mortality of brain tumours in the continents of Asia and Africa, especially in Indonesia, is thought to be due to the low reports of brain tumour disease from some of these countries, so as to increase knowledge and management of brain tumour plenary services in Indonesia, accurate hospital clinical data is needed. Objective: This study aims to look at the frequency of events, symptoms and clinical signs, histopathological characteristics, the stage at diagnosis, and compare the incidence of primary brain tumours in men and women. Methods: This study used a descriptive observational study design that uses data on primary brain tumour patients in the period of January 2017 - December 2018. Data collected includes clinical symptoms and signs, histopathological characteristics, and tumour tissue characteristics. Results: From 72 patients with primary brain tumour, only 36 (50%) of data can be used as samples due to the completeness of the medical record. The most common clinical symptoms and signs are headache, followed by limb disorders, and visual impairment. The most common histopathological features are Astrocytic tumour with a ratio of 17: 5 for men and women respectively. Conclusion: Primary brain tumours in RSUP Dr. Kariadi Semarang is often found with symptoms of headache followed by limb disorders and visual impairment, with a type of Astrocytic tumour that is more commonly found in men.